INFLUENCE OF SEX ON GROWTH PERFORMANCE, CARCASS ATTRIBUTES, MEAT QUALITY, AND BLOOD METABOLITES OF AWASSI LAMBS - Ja’far Al-Khaza’leh; Belal S. Obeidat (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study evaluated the effect of sex on growth performance, carcass characteristics, meat quality, and blood metabolite parameters of Awassi lambs. Twenty-seven Awassi lambs were allocated into two sex groups: males (n=13) and females (n=14). Lambs were individually penned and fed according to the nutritional needs of small ruminants. The experimental period of the study continued for 63 days, preceded by seven days for dietary and pen adaptation. On day 56 of the experimental period, five lambs of each sex group were randomly chosen and distributed in metabolism chambers to examine the digestibility and nitrogen balance. After 70 days of the trial, all lambs were butchered to determine their carcasses and meat quality. The average dry matter (DM) and crude protein (CP) intakes were significantly affected by sex (p < 0.05). Both sexes had similar DM and CP digestibility. Male lambs had greater nitrogen intake and retention (p < 0.05). Growth performance, weights of fasting animals, weights of hot and cold carcasses, non-carcass parts and carcass cuts were influenced (p < 0.05) by the lambs, sex.